2020
DOI: 10.1007/978-3-030-56223-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Feature Profiles of Web Shells by Analyzing the Performance of Multiple Detectors

Abstract: Web shells are commonly used to transfer malicious scripts in order to control web servers remotely. Malicious web shells are detected by extracting the feature profiles of known web shells and creating a learning model that classifies malicious samples. This chapter proposes a novel feature profile scheme for characterizing malicious web shells based on the opcode sequences and static properties of PHP scripts. A real-world dataset is employed to compare the performance of the feature profile scheme against s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, the dataset used in the experiments is not limited to 100 files, so more data is needed to validate the model. Huang et al [12] used 2 statistical features, 21 high-risk functions, and term frequency-inverse document frequency (TF-IDF) vectorization of PHP opcode sequences. They found that the random forest (RF) classifier outperformed the SVM and k-nearest neighbors (KNN) algorithms.…”
Section: Static Webshell Detectionmentioning
confidence: 99%
“…However, the dataset used in the experiments is not limited to 100 files, so more data is needed to validate the model. Huang et al [12] used 2 statistical features, 21 high-risk functions, and term frequency-inverse document frequency (TF-IDF) vectorization of PHP opcode sequences. They found that the random forest (RF) classifier outperformed the SVM and k-nearest neighbors (KNN) algorithms.…”
Section: Static Webshell Detectionmentioning
confidence: 99%